Three-phase tri-state buck-boost integrated inverter - De Brito, Moacyr A. G. [UNESP]; Canesin, Carlos A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2013)
This paper presents a three-phase integrated inverter suitable for stand-alone and/or grid-connected applications. The usage of the special features of the tri-state coupled with the special space vector modulation allows the inverter to present an attractive degree of freedom for the controllers' design, i.e. input and output can be controlled independently. Additionally all controllers are based on dq0 transformation, the system are described and interesting simulation results are available to confirm the proposal. Finally, this paper presents experimental evaluations of the inverter feeding a three-phase stand-alone load confirming the remarkable features of the decoupling control. © 2013 IEEE.
Keywords: Grid-Connected PV; Integrated Inverter; Space Vector Modulation; Stand-Alone PV; Three-Phase inverter